CONCEPTUAL METAPHORS IN THE LITERARY TEXTS - Koptileuova Hurliman; Dilyaram Ashurova (Scholar Express Journal, 2023)
This article deals with the problems of conceptual metaphors, the notion of conceptual metaphor as a cognitive model, a way of thinking, and one of the fundamental processes of human cognition, a specific way of conceptualizing information based on the mental process of analogy and knowledge transfer from one conceptual field into another. It is emphasized that conceptual metaphors has a crucial role in the representation of author’s individual worldpicture. Moreover, it helps determine the whole conceptual information in the literary text.
Keywords: conceptual; metaphors; cognitive mechanism; cognitive linguistics